+0  
 
0
46
2
avatar

what does this equal?

 

(2*sqrt(2)*e^t)^2 =

Guest Sep 20, 2017

Best Answer 

 #2
avatar+76878 
+1

(2*sqrt(2)*e^t)^2

 

Notice that   2sqrt(2)   = sqrt (4 * 2)   =  sqrt (8)

 

So we have

 

[ sqrt (8) * e^t ] ^2   =

 

[sqrt (8) ]2 * [ e]2  =

 

8 * e2t

 

 

cool cool cool

CPhill  Sep 20, 2017
Sort: 

2+0 Answers

 #1
avatar+116 
0

\(({2}^{2}*{e}^{t})^2=16{e}^{2t}\)

MagikalRedNiteTiger  Sep 20, 2017
 #2
avatar+76878 
+1
Best Answer

(2*sqrt(2)*e^t)^2

 

Notice that   2sqrt(2)   = sqrt (4 * 2)   =  sqrt (8)

 

So we have

 

[ sqrt (8) * e^t ] ^2   =

 

[sqrt (8) ]2 * [ e]2  =

 

8 * e2t

 

 

cool cool cool

CPhill  Sep 20, 2017

29 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details